MEREPOSISI PENGAJARAN BAHASA DAN SASTRA (Sumbang Saran untuk Mengurai Problem Pengajaran Bahasa dan Sastra) - Harimansyah, Ganjar (STILISTIKA, 2012)
MEREPOSISI PENGAJARAN BAHASA DAN SASTRA(Sumbang Saran untuk Mengurai Problem Pengajaran Bahasa dan Sastra)Ganjar HarimansyahBadan Pengembangan dan Pembinaan Bahasa Kemdikbud, JakartaPonsel: 0818700481 Pos-El: ganjar_hwi@yahoo.com                                                                               Abstract Learning the language and literature for a long time until now still has many obstacles and problems. On the other hand the problem implicitly keep expectations placed upon the teaching oflanguage and literature to contribute to achieving broadereducational goals. Problem and hope its certainly motivated the idea that language  and literary texts contain many aspects of lifewith the whole phenomenon. Including how to identify themselvesand the choice point of view to addressing the realities of spiritualand social Indonesia today. For acceleration purposes above,require the teaching of language and literature components of learning and teaching materials are superior, including theallocation of time and the subcomponents of learning methods.Which in the end, teaching language and literature can bemaximized to encourage the development of individual learners,creating a pleasant atmosphere, provide access to acquisition of new and different experiences, as well as stimulate the sensitivity of feelings, thought processes, and creativity of students. Key words: realignment, teaching, language and literature